The importance of the translator and interpreter in international relations: an analysis of Ricardo Palma’s «El primer cónsul inglés» - Borge Perez, Juan (2024)
In this research article, we will analyse the tradition «The First English Consul» by Ricardo Palma, based on the idea that, if Thomas Rowcroft had been able to speak correct Spanish or, in the second instance, had he had the help of a translator or interpreter, he could have escaped death, since his accessibility to the Spanish language would have prevented him from being seen as an easy prey by his assassins and would have facilitated better communication with those who could have saved his life. Behind this diplomatic case, in which a translator would have played a crucial role if he had been involved, lies the analysis of this text, which allows the recognition of an underlying and important theme: the role of the translator and interpreter in international relations, insofar as he or she must be a mediator between the representatives of two countries, whether they are friendly nations or in conflict, since his main function in this field is to facilitate understanding between societies and nations and to bring them together, as well as to facilitate recognition, communication and rapprochement between the cultural diversities that exist between peoples, thus being a bridge between cultures.